Blunt cerebrovascular injuries (Clinics, 2005)
Over the past decade, the recognition and subsequent management of blunt cerebrovascular injuries has undergone a marked evolution. Originally thought to be a rare occurrence, blunt cerebrovascular injuries are now diagnosed in approximately 1% of blunt trauma patients. The recognition of a clinically silent period allows for angiographic screening for injuries based upon the mechanism of trauma and the patient's constellation of injuries. Comprehensive screening of patients has resulted in the early diagnosis of blunt cerebrovascular injuries during the asymptomatic phase, thus allowing treatment that could prevent neurologic sequelae. Although the ideal regimen of antithrombotic therapy is yet to be determined, treatment with either antiplatelet or anticoagulant agents has been shown to reduce the blunt cerebrovascular injuries related stroke rate. Blunt cerebrovascular injury is a rare but potentially devastating injury; appropriate angiographic screening in high-risk patients should be performed and prompt treatment initiated to prevent ischemic neurologic events.